Persepsi Masyarakat Mengenai Penanganan Krisis Event Musik (Studi Kasus Festival Berdendang Bergoyang) - Mufid, Jazil Abdul; Alvansa, Moch; Sultana, Reyhan Daffa (Universitas Pendidikan Nasional, 2022)
This study aims to determine the public's views or perceptions of handling the crisis at the organizers of the